The mediating role of self-esteem on the relationship between perceived discrimination and mental health in South American immigrants in Chile. (January 2019) - Urzúa, Alfonso; Cabrera, Carlos; Carvajal, Carlos Calderón; Caqueo-Urízar, Alejandra
Highlights: The perception of discrimination influences physical and mental health. It is relevant to analyze the relationship between discrimination and mental health. Discrimination has a positive and direct relationship with both anxiety and depression. The effect of interaction between the variables of discrimination, self-esteem and symptoms associated with depression and anxiety, had a simple partial mediating effect. Abstract: Psychological aspects in South-South migration have been little studied. The following study aimed to describe the effect of individual self-esteem as a mediator in the relationship between perceived discrimination and mental health (understood as the presence of anxious and depressive symptomatology) in South American migrants in Chile. We surveyed 853 people, of Peruvian and Colombian nationality, residing in three cities (Arica, Antofagasta and Santiago). Three ad-hoc scales were applied to evaluate the study variables, analyzing the measurement models for each of them using the Confirmatory Factor Analysis method. Subsequently, the hypothesized mediation model is evaluated through Structural Equations (SEM). The results show that discrimination has a positive and direct relationship with both anxiety and depression, and that the effect of interaction between the variables of discrimination, self-esteem and symptoms associated with depression and anxiety, had a simple partial mediating effect. Discrimination would have a positive and minor effect on anxious and depressive symptoms, as it is mediated by self-esteem.